Recent Advances in Chemistry, Mechanism, and Applications of Quantum Dots in Photodynamic and Photothermal Therapy - Ranjbari, Faride; Fathi, Farzaneh (Anti-Cancer Agents in Medicinal Chemistry, 2024)
Semiconductor quantum dots (QD) are a kind of nanoparticle with unique optical properties that have attracted a lot of attention in recent years. In this paper, the characteristics of these nanoparticles and their applications in nanophototherapy have been reviewed. Phototherapy, including photodynamic therapy (PDT) and photothermal therapy (PTT), has gained special importance because of its high accuracy and local treatment due to the activation of the drug at the tumor site. PDT is a new way of cancer treatment that is performed by activating light-sensitive compounds named photosensitizers (PS) by light. PSs cause the destruction of diseased tissue through the production of singlet oxygen. PTT is another non-invasive method that induces cell death through the conversion of near-infrared light (NIR) into heat in the tumor situation by the photothermal agent (PA). Through using energy transfer via the FRET (Förster resonance energy transfer) process, QDs provide light absorption wavelength for both methods and cover the optical weaknesses of phototherapy agents.
Keywords: photodynamic therapy